El juego para potencializar la motricidad fina en los niños de inicial ii de la unidad educativa Lauro Damerval Ayora de la ciudad de Loja, en el periodo 2019-2020. - Sotomayor Pacheco, Vanessa Alejandra (2020)
The current investigation entitled THE GAME TO POTENTIALIZE FINE MOTOR IN CHILDREN OF INITIAL II OF THE LAURO DAMERVAL AYORA EDUCATIONAL UNIT OF THE CITY OF LOJA, IN THE PERIOD 2019-2020 had as a general objective to use the game to potentiate fine motor skills in the children of initial level II. In the development of the research, the scientific, analytical, synthetic and comparative methods were used, as a technique the survey with mixed questions and the instrument used was the Tepsi test. The study sample consisted of 3 pre-school teachers and 17 children from 4 to 5 years old. The diagnosis revealed that 83% of the total sample had the levels of delay and risk to acquire fine motor skills. After the application of the proposal based on children's games, an increase in motor skills to normal levels was evidenced in 76% of the sample. It is concluded that the alternative proposal based on games focused on improving motor skills had a positive impact, managing to enhance the fine motor aspect.